New early ripening variety of soybean. Anthracite - Білявська, Л. Г. (Scientific Progress & Innovations, 2012)
The new modern tasks in soybean selection, which are connected with soil-climatic conditions, varietal adaptability and considerable genetic culture potential are presented. Using sources of adaptability to limiting factors of environment by hybridization some new material has been created. This helped raise new soybean variety Anthracite. Early ripening highly productive variety Anthracite has been registered in the State Register of plants variety of Ukraine. Morphological description and economic aptitude of this sort are presented. The sort differs with its resistance to diseases and pests. The beans don’t burst. High capacity of protein and oil in seeds, quick moisture efficiency during ripening are particular qualities of the variety.